Nilai-Nilai Luhur bagi Orang Bajo di Desa Tapi-Tapi Kecamatan Marobo Kabupaten Muna - Feni Feni; Rahmat Sewa Suraya; Almarsaban Almarsaban (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study aims to determine and describe the Bajo people's views on noble values, and how the implementation of noble values for Bajo people in Tapi-Tapi Village, Marobo District, Muna Regency. The method used in the research is ethnographic method, researchers try to describe, describe and explain how the Bajo people view noble values-using in-depth observation and interview techniques. The data collected was then analyzed using Koentjaraningrat's theory of cultural values (1984). The Bajo people who live in Tapi-Tapi Village, Marobo District, Muna Regency are a fishing community that upholds noble values that have been passed down from generation to generation in the value of responsibility, namely: (a) Sipakkulong (supporting each other), (b) Mapulus jamaah itu dolo modi bunang (completing the work given), in the value of social care, namely: (a) Nggai kole sikalasa kadadarua (there should be no misunderstanding of others), (b) Sitabangang (helping each other in work), (c) Nggai kole mangasora'dialo (should not damage the sea), in the value of honesty, namely: (a) Nggai kole malaponggang aha sadiri (do not like to lie), in the value of independence, namely: (a) Ngajama diriang (work independently). The implementation of noble values for Bajo people is realized in several values, namely: (a) Si tuluh (helping), (b) Dianggo (mutual respect), (c) Sitabangang (cooperation) d Bapongka (group fishing activities).